Modified kaolin as well as preparation method and application thereof
By subjecting kaolin to high-temperature calcination and etching solution treatment, modified kaolin with abundant weak, medium, and strong alkaline sites on its surface was prepared, solving the problem of surface inertness of kaolin and expanding its applications in catalysts, fillers, ceramics, coatings, and pharmaceutical textiles.
Patent Information
- Application Number
- CN202410615480.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-17
- Publication Date
- 2025-11-18
AI Technical Summary
Existing kaolin catalyst materials have inert surfaces and lack unique surface alkaline properties, which limits their application in fields such as petrochemicals, wastewater treatment, and pharmaceutical synthesis.
Modified kaolin was obtained by calcining kaolin at high temperature and treating it with an etching solution to introduce alumina, silicon dioxide and modified metals to form weak, medium and strong alkaline sites on the surface. The modified kaolin was then obtained by filtration, washing, drying and calcination.
By endowing kaolin with unique surface acid-base properties, the preparation process is simplified, making it easier for industrial production and expanding its applications in catalysts, fillers, ceramics, coatings, and pharmaceutical textiles.
Smart Images

Figure BDA0004845107580000171 
Figure BDA0004845107580000172 
Figure BDA0004845107580000173
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, specifically to a modified kaolin, its preparation method, and its applications. Background Technology
[0002] Kaolin is an important and common industrial catalyst raw material. Due to its low specific surface area and low variety and density of surface active centers, it is often used as an inert matrix or filler. Modification can endow it with rich structural properties, thereby broadening its applications and making it more suitable for the iterative upgrading of synthesized materials (catalytic materials, filler materials, specialty materials, etc.). Numerous methods for modifying kaolin have been reported in the existing technology.
[0003] CN102188963A discloses a method for preparing modified kaolin, which involves adding high-temperature calcined kaolin, an external aluminum source, and an acidic solution into a container under stirring. After stirring until homogeneous, the mixture is reacted at 90-150℃. The resulting slurry can be used directly as a raw material for preparing catalytic cracking catalysts without filtration.
[0004] CN105983449A discloses a method for preparing a bottom oil catalytic cracking co-catalyst using kaolin. The method involves contacting calcined kaolin microspheres with an alkaline solution at room temperature to 100°C for at least 1 hour. The resulting slurry is then filtered and mixed with clay and a dispersant. After spraying, calcining, and ion exchange, a bottom oil catalytic cracking co-catalyst is obtained.
[0005] CN100478069A discloses a method for modifying kaolin, which involves mixing kaolin, a dispersant modifier, an acid solution, and deionized water, followed by pulping, calcination, cooling, and washing to obtain modified kaolin. Using the modified kaolin as a matrix for cracking catalysts, the catalytic activity of heavy oil cracking and gasoline yield are improved, while the dry gas yield is reduced.
[0006] CN109692702A discloses a method for preparing macroporous kaolinite, which involves mixing calcined kaolin with an acidic compound and a modified metal compound, followed by recalcination and mixing with an acidic solution, a pore-expanding agent, and the modified metal to obtain macroporous kaolinite. The macroporous kaolinite exhibits high cracking activity and can be used to prepare cracking catalysts. The resulting catalysts show high gasoline yield and gasoline octane number, but low coke selectivity.
[0007] None of the aforementioned existing technologies report how to endow kaolin with unique surface alkaline properties, which have wide applications in petrochemicals, wastewater treatment, and pharmaceutical synthesis. Therefore, developing a modified kaolin with unique surface alkaline properties is of great significance to the development of these fields. Summary of the Invention
[0008] The technical problem to be solved by the present invention is to provide a modified kaolin and its preparation method to overcome the inertness of existing kaolin used for catalyst preparation.
[0009] In a first aspect, the present invention provides a modified kaolin containing 30-70 wt% alumina, 30-70 wt% silica, and 0-40 wt% modified metal (calculated as oxides), wherein the modified metal is selected from one or more of IA, IIA, IVB, and lanthanide metals; in the modified kaolin, the density of weakly basic sites on the surface is 50-1000 μmol / g, the density of moderately basic sites is 100-3000 μmol / g, the density of strongly basic sites is 60-2000 μmol / g, and the density of weakly acidic sites on the surface is 0.01-10 μmol / g, and the surface of the modified kaolin does not contain strongly acidic sites.
[0010] In this invention, the surface alkaline sites are defined and corresponding to the CO2 desorption temperature in the CO2-TPD test, and the surface acidic sites are defined and corresponding to the NH3 desorption temperature in the NH3-TPD test.
[0011] Specifically, in the CO2-TPD test, a CO2 desorption temperature <200℃ corresponds to the weakly basic site, a CO2 desorption temperature between 200-600℃ corresponds to the moderately basic site, and a CO2 desorption temperature ≥600℃ corresponds to the strongly basic site; in the NH3-TPD test, an NH3 desorption temperature <200℃ corresponds to the weakly acidic site, an NH3 desorption temperature between 200-600℃ corresponds to the moderately acidic site, and an NH3 desorption temperature ≥600℃ corresponds to the strongly basic site.
[0012] Secondly, the present invention provides a method for preparing modified kaolin, comprising the following steps:
[0013] (1) Kaolin is calcined at 400-1200℃ for 0.5-10h to obtain metakaolin;
[0014] (2) Mix metakaolin with water to obtain metakaolin slurry, and process the metakaolin slurry with a shearing machine to obtain slurry metakaolin;
[0015] (3) Mix peroxide, inorganic-organic composite alkali, ionic surfactant, quinoline substances and oil in a mass ratio of 1:0.1-18:0.5-5:0.4-5:0.1-8, and adjust the pH of the mixture to 9-14 to obtain etching solution;
[0016] (4) Mix the etching solution and the slurry metakaolin evenly, wherein the mass ratio of the etching solution to the metakaolin is 0.2-3:1. During the mixing process, a modified metal salt solution may or may not be added to obtain a modified mixture.
[0017] (5) The modified mixture is filtered, washed, dried and calcined to obtain modified kaolin.
[0018] Thirdly, the present invention provides the application of the above-mentioned modified kaolin in catalysts, fillers, ceramics, coatings, pharmaceuticals and textiles.
[0019] Compared with the prior art, the beneficial effects of the modified kaolin and its preparation method provided by the present invention are as follows:
[0020] (1) The modified kaolin provided by the present invention has unique surface acid-base properties. Specifically, its surface has abundant weak, medium and strong alkaline sites, and the modified kaolin surface has acidic sites with low density. The modified kaolin presents as a plate-like aggregate with a dispersed pore size distribution.
[0021] (2) The modified kaolin preparation method provided by the present invention simplifies the process flow and facilitates industrial production; in particular, by limiting the formulation of the etching solution, the acid-base properties of the kaolin surface can be controlled.
[0022] (3) The modified kaolin provided by the present invention can be applied in the fields of catalysts, fillers, ceramics, coatings, pharmaceuticals and textiles. Attached Figure Description
[0023] Figure 1 The CO2-TPD spectra of the modified kaolinite prepared in Example 1 and Comparative Examples 1-2 are shown.
[0024] Figure 2 The NH3-TPD spectra of the modified kaolinite prepared in Example 1 and Comparative Examples 1-2 are shown.
[0025] Figure 3 The N2 isotherm adsorption curve of the modified kaolin prepared in Example 1 is shown.
[0026] Figure 4 The image shows the pore size distribution of the modified kaolin prepared in Example 1. Detailed Implementation
[0027] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the invention. The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values; these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0028] In a first aspect, the present invention provides a modified kaolin containing 30-70 wt% alumina, 30-70 wt% silicon dioxide, and 0-40 wt% modified metal (based on metal oxides), wherein the modified metal is selected from one or more of IA, IIA, IVB and lanthanide metals; in the modified kaolin, the density of weakly basic sites on the surface is 50-1000 μmol / g, the density of moderately basic sites is 100-3000 μmol / g, the density of strongly basic sites is 60-2000 μmol / g, and the density of weakly acidic sites on the surface is 0.01-10 μmol / g, and the surface of the modified kaolin does not contain strongly acidic sites.
[0029] In this invention, the surface alkaline sites are defined and corresponding to the CO2 desorption temperature in the CO2-TPD test, and the surface acidic sites are defined and corresponding to the NH3 desorption temperature in the NH3-TPD test.
[0030] Specifically, in the CO2-TPD test, a CO2 desorption temperature <200℃ corresponds to the weakly basic site, a CO2 desorption temperature between 200-600℃ corresponds to the moderately basic site, and a CO2 desorption temperature ≥600℃ corresponds to the strongly basic site; in the NH3-TPD test, an NH3 desorption temperature <200℃ corresponds to the weakly acidic site, an NH3 desorption temperature between 200-600℃ corresponds to the moderately acidic site, and an NH3 desorption temperature ≥600℃ corresponds to the strongly basic site.
[0031] Preferably, the modified kaolin contains 30-48 wt% alumina, 30-52 wt% silicon dioxide, and 0-30 wt% modified metal (based on oxides). More preferably, the modified kaolin contains 30-48 wt% alumina, 37-52 wt% silicon dioxide, and 1-15 wt% modified metal.
[0032] Preferably, the modified kaolin has a specific surface area of 30-80 m². 2 / g, preferably 40-50m 2 / g.
[0033] Preferably, the density of weakly alkaline sites on the surface of the modified kaolin is 80-600 μmol / g; the density of moderately alkaline sites is 120-1600 μmol / g; and the density of strongly alkaline sites is 80-1400 μmol / g.
[0034] Preferably, the density of weakly acidic sites on the surface of the modified kaolin is 0.04-5 μmol / g, and the surface of the modified kaolin does not contain strongly acidic sites.
[0035] Preferably, the modified metal component is selected from one or more of the IA, IIA, IVB, and lanthanide metals.
[0036] The inventors of this disclosure discovered during their research that kaolin is a surface-inert mineral widely used in catalysts, coatings, enamels, and building materials. Surface etching imparts unique alkaline properties to kaolin, expanding its applications in catalyst preparation. Through high-temperature activation, slurry shearing, and etching solution treatment, kaolin can be endowed with abundant alkaline sites on its surface, resulting in a surface exhibiting high density of weakly alkaline, moderately alkaline, and strongly alkaline properties, as well as a weakly acidic surface characteristic.
[0037] In one specific embodiment of the present invention, based on the total weight of the modified kaolin, the alumina content is 30-70 wt%; the silica content is 30-70 wt%, and it does not contain any modified metal components. In the modified kaolin, the density of weakly basic sites on the surface is 50-1000 μmol / g, the density of moderately basic sites is 100-3000 μmol / g, the density of strongly basic sites is 60-2000 μmol / g, and the density of weakly acidic sites on the surface is 0.01-10 μmol / g. The modified kaolin surface does not contain strongly acidic sites.
[0038] In a preferred embodiment of the present invention, based on the total weight of the modified kaolin, the modified kaolin contains 30-48 wt% alumina, 37-52 wt% silicon dioxide, and, as metal oxides, the content of modified metal is 1-15 wt%. In the modified kaolin, the density of weakly basic sites on the surface is 50-1000 μmol / g, the density of moderately basic sites is 100-3000 μmol / g, the density of strongly basic sites is 60-2000 μmol / g, and the density of weakly acidic sites on the surface is 0.01-10 μmol / g. The surface of the modified kaolin does not contain strongly acidic sites.
[0039] In a preferred embodiment of the present invention, the specific surface area of the modified kaolin is 30-80 m². 2 / g.
[0040] In a preferred embodiment of the present invention, the specific surface area of the modified kaolin is 40-50 m². 2 / g.
[0041] In this invention, the modified metal component can be selected from one or a mixture of several of the IA, IIA, IVB, and lanthanides. In a preferred embodiment, the modified metal component is selected from one or more of sodium, potassium, magnesium, calcium, zirconium, lanthanum, and cerium.
[0042] Secondly, the present invention provides a method for preparing modified kaolin, comprising the following steps:
[0043] (1) Kaolin is calcined at 400-1200℃ for 0.5-10h to obtain metakaolin;
[0044] (2) Mix metakaolin with water to obtain metakaolin slurry, and process the metakaolin slurry with a shearing machine to obtain slurry metakaolin;
[0045] (3) Mix peroxide, inorganic-organic composite alkali, ionic surfactant, quinoline substances and oil in a mass ratio of 1:0.1-18:0.5-5:0.4-5:0.1-8, and adjust the pH of the mixture to 9-14 to obtain etching solution;
[0046] (4) Mix the etching solution and the slurry metakaolin evenly, wherein the mass ratio of the etching solution to the metakaolin is 0.2-3:1. During the mixing process, a modified metal salt solution may or may not be added to obtain a modified mixture.
[0047] (5) The modified mixture is filtered, washed, dried and calcined to obtain modified kaolin.
[0048] In this invention, the peroxide is a compound containing a peroxide bond. The inorganic-organic complex base is a homogeneous mixture of one or more inorganic and organic bases, wherein the organic base is a glycine betaine analogue. The oil is a fat or aromatic substance extracted from petroleum or plants.
[0049] Preferably, the peroxide is one or more of H2O2, Na2O2, and peracetic acid; the inorganic-organic composite alkali is a mixture of inorganic and organic alkalis, wherein the inorganic alkali is selected from one or more of sodium hydroxide, potassium hydroxide, ammonia, sodium phosphate, anhydrous borax, anhydrous sodium carbonate, anhydrous potassium carbonate, sodium silicate, sodium orthosilicate, and sodium acetate; and the organic alkali is selected from proline betaine, trigonelline, alanine betaine, valine betaine, piperic acid betaine, aminopentaenoic acid betaine, N-trimethylammonium trioxide, and N-trimethylammonium trioxide. The active ingredient is selected from one or more of methyl lysine, arsenopyrine, γ-butyryl betaine, and ergothioneine; the ionic surfactant is selected from branched or straight-chain hydrocarbons with hydrophilic groups of carboxylic acids, sulfonic acids, sulfuric acids, amino acids and their salts, and hydrophobic groups of C10-C16; the quinoline substance is selected from one or more of 4-hydroxyquinoline, 8-hydroxyquinoline, quinolinone, acetaminophenquinoline, and quinine; the oil is selected from one or more of naphtha, lubricating oil, jet fuel, kerosene, diesel oil, peanut oil, perilla oil, and tea tree oil.
[0050] More preferably, the peroxide is hydrogen peroxide and / or peracetic acid, the inorganic base is ammonia, sodium hydroxide or sodium phosphate, the organic base is proline betaine or γ-butyryl betaine, the ionic surfactant is potassium dodecylbenzenesulfonate, hexadecyltrimethylammonium chloride or dodecylamine, the phenolic antioxidant is 4-hydroxyquinoline or quinoline ketone, and the oil is selected from one or more of lubricating oil, naphtha and diesel.
[0051] In this invention, step (4) involves a wide range of choices for the modified metal salt, and this invention does not limit this selection. Preferably, the modified metal salt is selected from chlorides, nitrates, sulfates, and phosphates of IA, IIA, IVB, and lanthanide metals. Preferably, the modified metal salt solution is selected from aqueous solutions of chlorides, nitrates, or sulfates of IA, IIA, IVB, and lanthanide metals. The mass concentration of the metal salt in the modified metal salt solution is 5-30 wt%. In embodiments where the modified metal solution is added, the modified kaolin obtained has a modified metal content of 0.5 wt%-40 wt%, calculated as metal oxides.
[0052] The modified kaolin preparation method provided by the present invention preferably includes the following steps: in step (1), the calcination temperature is 600-900℃ and the calcination time is 2-6h; in step (2), the mass ratio of kaolin to water is 1:0.5-20, preferably 1:2-10; and the particle size of the solid particles in the slurry metakaolin obtained by shearing is 5nm-20μm, preferably 10nm-15μm.
[0053] Preferably, in step (3), the mass ratio of peroxide, inorganic-organic composite alkali, ionic surfactant, quinoline-like substance, and oil is 1:0.2-6:0.5-3:0.4-2:0.3-5. The etching solution is prepared at a temperature of 0-35℃, preferably 10-25℃; it is mixed using a stirrer at a speed of 50-1000 rpm, preferably 300-1000 rpm; and the stirring time is 0.5-10 h, preferably 1-3 h. The pH of the mixture is adjusted to 9-14 using an alkaline solution, preferably ammonia, to obtain the etching solution.
[0054] Preferably, in step (4), the modified metal salt solution is injected into the mixture of etching solution and slurry metakaolin, with a pumping speed of 0.1-20 mL / min, preferably 0.5-10 mL / min.
[0055] Preferably, in step (5), the drying temperature of the mixture is 80-150℃, more preferably 100-120℃; the calcination temperature is 400-1000℃, and the calcination time is 1-10h; preferably, the calcination temperature is 500-900℃, and the calcination time is 2-5h.
[0056] In this invention, the amount of kaolin and water added in step (2) is sufficient to prepare a slurry. In step (3), preferably, the mass ratio of peroxide, inorganic-organic composite alkali, ionic surfactant, quinoline-like substance and oil is 1:0.1-18:0.5-5:0.4-5:0.1-8, and more preferably 1:0.2-6:0.5-3:0.4-2:0.3-5.
[0057] In this invention, peroxides and inorganic-organic composite bases are the core active components of the etching solution. Ionic surfactants, quinoline substances and oils are additives that can inhibit the decomposition of active components and enable the core active components to have better mixing / dispersion effects, thereby causing the metakaolin surface skeleton, which is mainly composed of Al-O-Si bonds, to dissociate and obtain alkaline sites.
[0058] Thirdly, the present invention provides the application of the above-mentioned modified kaolin in catalysts, fillers, ceramics, coatings, pharmaceuticals and textiles.
[0059] The specific implementation methods and technical effects of the present invention will be further described below with reference to the embodiments and accompanying drawings, but the accompanying drawings and embodiments do not constitute a limitation on the present invention.
[0060] In the examples and comparative examples:
[0061] The kaolin raw material is Suzhou kaolin, and other chemical reagents are obtained from the market.
[0062] The contents of alumina, silicon dioxide and modified metal components in the modified alumina were determined by X-ray fluorescence spectrometry (XRF).
[0063] The specific surface area parameter was measured using a fully automated isothermal adsorption instrument.
[0064] Alkali density and alkali content were measured using carbon dioxide-programmed temperature desorption (CO2-TPD). Among them, the CO2 desorption temperature range of 50-200℃ represents the CO2 desorption peak of weakly basic sites, the range of 200-600℃ represents the CO2 desorption peak of moderately basic sites, and the range of 600-800℃ represents the CO2 desorption peak of strongly basic sites.
[0065] Acid density and acid content were measured using amino-programmed temperature desorption (NH3-TPD). Among them, the NH3 desorption temperature range of 50-200℃ represents the NH3 desorption peak of weakly basic sites, the range of 200-600℃ represents the NH3 desorption peak of moderately basic sites, and the range of 600-800℃ represents the NH3 desorption peak of strongly basic sites.
[0066] The particle size of the slurry kaolin was measured using a dynamic light scattering particle size analyzer.
[0067] Example 1
[0068] (1) 2 kg of kaolin was calcined at 600℃ for 3 h to obtain metakaolin;
[0069] (2) Mix 1 kg of metakaolin with 1.5 kg of water at high speed and stir well, and then process the slurry metakaolin using a shearing machine;
[0070] (3) At 10℃, 50g of 20wt% H2O2, 220g of sodium phosphate-N-trimethyllysine complex base, 30g of potassium dodecylbenzenesulfonate, 40g of 8-hydroxyquinoline and 20g of lubricating oil were stirred evenly at a stirring rate of 800rpm for 1h. The pH was adjusted to 10 to obtain etching solution K1.
[0071] (4) Mix 300g of etching solution K1 described in step (3) with 1kg of slurry metakaolin. During the mixing process, slowly add 1000mL of 3wt% MgCl2 solution. The MgCl2 solution is pumped in at a rate of 8mL / min to obtain a mixture.
[0072] (5) The mixture is filtered and washed until pH is neutral, and dried at 120°C to obtain a dried product; the dried product is calcined at 600°C for 2 hours to obtain modified kaolin S1.
[0073] The CO2-TPD spectrum of modified kaolin S1 is attached. Figure 1 As shown, by appendix Figure 1 It can be seen that modified kaolin S1 has absorption peaks at 50-200℃, 200-600℃, and 60-800℃, corresponding to a density of 253.1 μmol / g for weakly alkaline sites, 1282.2 μmol / g for moderately alkaline sites, and 1388.9 μmol / g for strongly alkaline sites on its surface.
[0074] The NH3-TPD spectrum of modified kaolin S1 is attached. Figure 2 As shown, by appendix Figure 2 It can be seen that the modified kaolin S1 has no obvious absorption peak at 100-200℃ and no absorption peak at 200-600℃, corresponding to its low surface acidity density. The analysis shows that the density of weakly acidic sites on the surface is 0.7 μmol / g, and the modified kaolin surface does not contain strongly acidic sites.
[0075] The composition and physical properties of modified kaolin S1 are listed in Table 1-1. The surface acid-base properties are listed in Table 2-1.
[0076] Appendix Figure 3 The N2 isotherm adsorption curve of modified kaolin S1, with... Figure 4 This is a pore size distribution diagram of modified kaolin S1; from the attached diagram. Figure 3 Calculations can yield the attached... Figure 4 From the appendix Figure 3 It can be seen that the N2 physical adsorption curve of modified kaolin S1 is an H3-type hysteresis loop, showing no adsorption limitation in the higher relative pressure region; and, attached... Figure 4 This is a typical pore size distribution pattern characteristic of sheet-like materials; the material does not have a relatively concentrated pore size distribution range. (Appendix) Figure 3 With appendix Figure 4 This indicates that the modified kaolin S1 prepared by this invention has an irregular lamellar structure and irregular pore size.
[0077] Example 2
[0078] (1) 1 kg of kaolin was calcined at 900℃ for 2 h to obtain metakaolin;
[0079] (2) Mix 1 kg of metakaolin with 4 kg of water at high speed and stir well, and then use a shearing machine to process the slurry metakaolin;
[0080] (3) At 15℃, 30g of 20wt% peracetic acid, 90g of potassium hydroxide-proline betaine complex base, 30g of dodecyl dimethylamine oxide, 40g of 4-hydroxyquinoline and 150g of perilla oil were stirred evenly at a stirring rate of 600rpm for 2h. The pH was adjusted to 12 to obtain etching solution K2.
[0081] (4) Mix 400g of etching solution K2 described in step (3) with 800g of slurry metakaolin. During the mixing process, slowly add 100mL of 10wt% NaNO3 solution. The NaNO3 solution is pumped in at a rate of 5mL / min to obtain a mixture.
[0082] (5) The mixture is filtered and washed until pH neutral, and dried at 100°C to obtain a dried product; the dried product is calcined at 800°C for 3 hours to obtain modified kaolin S2. The composition and physical properties of modified kaolin S2 are listed in Table 1-1. The surface acid-base properties are listed in Table 2-1.
[0083] Example 3
[0084] (1) 3 kg of kaolin was calcined at 800℃ for 2 h to obtain metakaolin;
[0085] (2) Mix 2 kg of metakaolin with 30 kg of water at high speed and stir well, and then use a shearing machine to process the slurry metakaolin;
[0086] (3) At 25℃, 90g of 20wt% H2O2, 400g of sodium silicate-piperacyl betaine composite alkali, 120g of hexadecyltrimethylammonium chloride, 100g of quinolinone and 60g of diesel oil were stirred evenly at a stirring rate of 800rpm for 3h. The pH was adjusted to 14 to obtain etching solution K3.
[0087] (4) Mix 1 kg of etching solution K3 described in step (3) with 1.5 kg of slurry metakaolin. During the mixing process, slowly add 500 mL of 5 wt% La(NO3)3 solution. The La(NO3)3 solution is pumped in at a rate of 6 mL / min to obtain a mixture.
[0088] (5) The mixture is filtered and washed until pH is neutral, and dried at 100°C to obtain a dried product; the dried product is calcined at 600°C for 5 hours to obtain modified kaolin S3.
[0089] The composition and physical properties of modified kaolin S3 are listed in Table 1-1. The surface acid-base properties are listed in Table 2-1.
[0090] Example 4
[0091] (1) 2 kg of kaolin was calcined at 600℃ for 5 h to obtain metakaolin;
[0092] (2) Mix 2 kg of metakaolin with 40 kg of water at high speed and stir well, and then process the slurry metakaolin using a shearing machine;
[0093] (3) At 5℃, 50g of 20wt% H2O2, 100g of potassium carbonate-γ-butyryl betaine complex base, 120g of hexadecyltrimethylammonium chloride, 180g of quinolinone and 20g of peanut oil were stirred evenly at a stirring rate of 500rpm for 1h. The pH was adjusted to 14 to obtain etching solution K4.
[0094] (4) Mix 400g of etching solution K4 described in step (3) with 2kg of slurry metakaolin. During the mixing process, slowly add 500mL of 5wt% zirconium oxynitrate solution. The zirconium oxynitrate solution is pumped in at a rate of 10mL / min to obtain a mixture.
[0095] (5) The mixture is filtered and washed until pH is neutral, and dried at 120°C to obtain a dried product; the dried product is calcined at 800°C for 2 hours to obtain modified kaolin S4.
[0096] The composition and physical properties of modified kaolin S4 are listed in Table 1-1. The surface acid-base properties are listed in Table 2-1.
[0097] Example 5
[0098] (1) 2 kg of kaolin was calcined at 1000℃ for 2 h to obtain metakaolin;
[0099] (2) Mix 2 kg of metakaolin with 5 kg of water at high speed and stir well, and then process the slurry metakaolin using a shearing machine;
[0100] (3) At 5℃, 60g of 20wt% Na2O2, 100g of sodium orthosilicate-aminopentane betaine complex alkali, 80g of sodium decaalkylbenzene sulfonate, 60g of quinine and 50g of peanut oil were stirred evenly at a stirring rate of 700rpm for 1h. The pH was adjusted to 12 to obtain etching solution K5.
[0101] (4) Mix 350g of etching solution K5 described in step (3) with 1.8kg of slurry metakaolin. During the mixing process, slowly add 300mL of 6wt% Na2SO4 solution. The Na2SO4 solution is pumped in at a rate of 8mL / min to obtain a mixture.
[0102] (5) The mixture is filtered and washed until the pH is neutral, and dried at 100°C to obtain a dried product; the dried product is calcined at 600°C for 3 hours to obtain modified kaolin S5.
[0103] The composition and physical properties of modified kaolin S5 are listed in Table 1-1. The surface acid-base properties are listed in Table 2-1.
[0104] Example 6
[0105] (1) 3 kg of kaolin was calcined at 600℃ for 3 h to obtain metakaolin;
[0106] (2) Mix 3 kg of metakaolin with 3 kg of water at high speed and stir until homogeneous, and then process the slurry metakaolin using a shearing machine;
[0107] (3) At 15℃, 20g of 20wt% H2O2, 800g of ammonia-valine betaine compound base, 120g of sodium tetradecyl sulfonate, 60g of quinoline and 10g of tea tree oil were stirred evenly at a stirring rate of 600rpm for 3h. The pH was adjusted to 12 to obtain etching solution K6.
[0108] (4) Mix 1000g of etching solution K6 described in step (3) with 1.2kg of slurry metakaolin. During the mixing process, slowly add 300mL of 10wt% Ce(NO3)3 solution. The Ce(NO3)3 solution is pumped in at a rate of 3mL / min to obtain a mixture.
[0109] (5) The mixture is filtered and washed until pH is neutral, and dried at 100°C to obtain a dried product; the dried product is calcined at 600°C for 3 hours to obtain modified kaolin S6.
[0110] The composition and physical properties of modified kaolin S6 are listed in Table 1-2. The surface acid-base properties are listed in Table 2-2.
[0111] Example 7
[0112] (1) 1 kg of kaolin was calcined at 800℃ for 2 h to obtain metakaolin;
[0113] (2) Mix 1 kg of metakaolin with 6 kg of water at high speed and stir well, and then process the slurry metakaolin using a shearing machine;
[0114] (3) At 35℃, 50g of 20wt% H2O2, 500g of sodium orthosilicate-valine betaine complex alkali, 120g of sodium dodecyl sulfate, 20g of 8-hydroxyquinoline and 10g of rapeseed oil were stirred evenly at a stirring rate of 900rpm for 1h. The pH was adjusted to 13 to obtain etching solution K7.
[0115] (4) Mix 600g of etching solution K7 described in step (3) with 1kg of slurry metakaolin. During the mixing process, slowly add 300mL of 10wt% CaSO4 solution. The CaSO4 solution is pumped in at a rate of 6mL / min to obtain a mixture.
[0116] (5) The mixture is filtered and washed until pH is neutral, and dried at 120°C to obtain a dried product; the dried product is calcined at 800°C for 5 hours to obtain modified kaolin S7.
[0117] The composition and physical properties of modified kaolin S7 are listed in Table 1-2. The surface acid-base properties are listed in Table 2-2.
[0118] Example 8
[0119] (1) 2 kg of kaolin was calcined at 900℃ for 1 h to obtain metakaolin;
[0120] (2) Mix 1 kg of metakaolin with 5 kg of water at high speed and stir well, and then use a shearing machine to process the slurry metakaolin;
[0121] (3) At 5℃, 50g of 20wt% Na2O2, 200g of KOH-valine betaine compound base, 100g of potassium hexadecyl sulfate, 40g of 4-hydroxyquinoline and 30g of lubricating oil were stirred evenly at a stirring rate of 600rpm for 2h. The pH was adjusted to 14 to obtain etching solution K8.
[0122] (4) Mix 400g of etching solution K8 described in step (3) with 1kg of slurry metakaolin. During the mixing process, slowly add 500mL of 10wt% KCl solution. The KCl solution is pumped in at a rate of 5mL / min to obtain a mixture.
[0123] (5) The mixture is filtered and washed until pH is neutral, and dried at 120°C to obtain a dried product; the dried product is calcined at 600°C for 4 hours to obtain modified kaolin S8.
[0124] The composition and physical properties of modified kaolin S8 are listed in Table 1-2. The surface acid-base properties are listed in Table 2-2.
[0125] Example 9
[0126] (1) 2 kg of kaolin was calcined at 600℃ for 3 h to obtain metakaolin;
[0127] (2) Mix 2 kg of metakaolin with 6 kg of water at high speed and stir well, and then process the slurry metakaolin using a shearing machine;
[0128] (3) At 10℃, 40g of 20wt% H2O2, 200g of anhydrous potassium carbonate-proline betaine compound base, 160g of dodecylamine, 70g of quinolinone and 50g of kerosene were stirred evenly at a stirring rate of 900rpm for 2h and the pH was adjusted to 11 to obtain etching solution K9.
[0129] (4) Mix 450g of the etching solution K9 described in step (3) with 2kg of slurry metakaolin to obtain a mixture;
[0130] (5) The mixture is filtered and washed until pH is neutral, and dried at 100°C to obtain a dried product; the dried product is calcined at 600°C for 2 hours to obtain modified kaolin S9.
[0131] The composition and physical properties of modified kaolin S9 are listed in Table 1-2. The surface acid-base properties are listed in Table 2-2.
[0132] Example 10
[0133] (1) 2 kg of kaolin was calcined at 800℃ for 2 h to obtain metakaolin;
[0134] (2) Mix 1 kg of metakaolin with 5 kg of water at high speed and stir well, and then use a shearing machine to process the slurry metakaolin;
[0135] (3) At 5℃, 40g of 20wt% H2O2, 200g of sodium silicate-glycine betaine composite alkali, 150g of hexadecylamine, 100g of quinoline and 40g of fuel oil were stirred evenly at a stirring rate of 900rpm for 3h. The pH was adjusted to 12 to obtain etching solution K10.
[0136] (4) Mix 500g of etching solution K10 described in step (3) with 500g of slurry metakaolin. During the mixing process, slowly add 600mL of 25wt% magnesium phosphate solution. The magnesium phosphate solution is pumped in at a rate of 10mL / min to obtain a mixture.
[0137] (5) The mixture is filtered and washed until pH is neutral, and dried at 100°C to obtain a dried product; the dried product is calcined at 700°C for 3 hours to obtain modified kaolin S10.
[0138] The composition and physical properties of modified kaolin S10 are listed in Table 1-3. The surface acid-base properties are listed in Table 2-2.
[0139] Comparative Example 1
[0140] Following the method of Example 1, except that no etching solution treatment process was performed to obtain DS1.
[0141] The CO2-TPD spectrum of modified kaolin DS1 is shown in the attached figure. Figure 1 As shown, by appendix Figure 1 It can be seen that the modified kaolin DS1 has a weak absorption peak in the range of 50-300℃, and no obvious absorption peak in the range of 300-600℃ and 600-800℃, and its surface alkali density is low.
[0142] The NH3-TPD spectrum of modified kaolin DS1 is attached. Figure 2 As shown, by appendix Figure 2 It can be seen that modified kaolin DS1 has an absorption peak at 150-300℃ and its acid density is relatively low.
[0143] The composition and physical properties of modified kaolin DS1 are listed in Table 1-3. The surface acid-base properties are listed in Table 2-3.
[0144] Comparative Example 2
[0145] The method of Example 1 is different except that in step (3), no inorganic-organic complex base is added to obtain DS2.
[0146] The CO2-TPD spectrum of modified kaolin DS2 is attached. Figure 1 As shown, by appendix Figure 1 It can be seen that the modified kaolin DS2 has a weak absorption peak in the range of 50-300℃, and no obvious absorption peak in the ranges of 300-600℃ and 600-800℃. The alkali density of modified kaolin DS2 is low.
[0147] The NH3-TPD spectrum of modified kaolin DS2 is attached. Figure 2 As shown, by appendix Figure 2 It can be seen that modified kaolin DS2 has an absorption peak at 150-300℃ and its acid density is relatively low.
[0148] The composition and physical properties of modified kaolin DS2 are listed in Table 1-3. The surface acid-base properties are listed in Table 2-3.
[0149] Comparative Example 3
[0150] The method of Example 1 is different except that in step (3), no surfactants and oils are added to obtain DS3.
[0151] The composition and physical properties of modified kaolin DS3 are listed in Table 1-3. The surface acid-base properties are listed in Table 2-3.
[0152] Table 1-1
[0153]
[0154] Table 1-2
[0155]
[0156] Table 1-3
[0157]
[0158]
[0159] Table 2-1
[0160]
[0161] Table 2-2
[0162]
[0163] Table 2-3
[0164]
[0165] Example 11
[0166] Catalyst Preparation and Evaluation Examples
[0167] 1 kg of modified matrix S1, 0.8 kg of Y-type molecular sieve, 0.2 kg of pseudoboehmite, 0.13 kg of alumina sol (20 wt%) and 5 kg of water were mixed and pulped at a stirring speed of 500 rpm and a temperature of 15℃. The slurry was then spray-dried at an inlet temperature of 400℃ and an outlet temperature of 160℃ to obtain a microspherical catalyst precursor. The microspherical catalyst precursor was calcined at 600℃ to obtain catalyst SS1 based on the modified matrix.
[0168] Catalyst evaluation conditions: 2 kg catalyst samples (Example SS1 or Comparative Example SS2) were evaluated in a fixed-bed microreactor. The feedstock was Daqing vacuum residue. The catalyst aging temperature was 790℃, and the water vapor (100% content) was introduced for 17 h during the aging process. The catalytic reaction temperature was 600℃.
[0169] The test results are listed in Table 3. In Table 3, "light oil slurry" specifically refers to "gasoline + diesel".
[0170] Comparative Example 4
[0171] Catalyst preparation and evaluation comparative example
[0172] The modified matrix S1 in the above catalyst preparation example SS1 was replaced with unmodified kaolin, while other processes and raw material amounts were the same as in SS1, to obtain catalyst SS2 based on the unmodified matrix.
[0173] The catalyst evaluation method is the same as in Example 1 of catalyst preparation and evaluation. The test results are shown in Table 3.
[0174] Table 3
[0175] Example 11 Comparative Example 4 catalyst SS1 SS2 Cracking product distribution, wt% propylene 22.4 23.3 ethylene 18.0 17.4 Light oil slurry 42.7 37.6 coke 9.0 13.3 methane 7.9 8.4
[0176] The results in Tables 1-1, 1-2, 1-3, 2-1, 2-2, and 2-3 show that, compared to Comparative Examples 1-3, the modified kaolin prepared in Examples 1-10 possesses unique surface acid-base properties. Its surface simultaneously exhibits abundant weak, medium, and strong alkaline sites, and also contains weakly acidic sites with a low density. The modified kaolin presents as plate-like aggregates with irregular pore sizes. Furthermore, the evaluation test results of catalysts SS1 and SS2 in Table 3 indicate that kaolin with the above properties can be added as an additive to catalytic reactions using alkaline catalysts to reduce coke production and increase the yield of light oil slurry products. The modified kaolin provided by this invention can be applied in catalysts, fillers, ceramics, coatings, pharmaceuticals, textiles, and other fields.
Claims
1. A modified kaolin, characterized in that, The modified kaolin contains 30-70 wt% alumina, 30-70 wt% silica, and 0-40 wt% modified metal (based on oxides), wherein the modified metal is selected from one or more of IA, IIA, IVB, and lanthanide metals; the density of weakly alkaline sites on the surface of the modified kaolin is 50-1000 μmol / g, the density of moderately alkaline sites is 100-3000 μmol / g, the density of strongly alkaline sites is 60-2000 μmol / g, and the density of weakly acidic sites on the surface is 0.01-10 μmol / g; the surface of the modified kaolin does not contain strongly acidic sites.
2. The modified kaolin according to claim 1, characterized in that, The specific surface area of the modified kaolin is 30-80 m². 2 / g, preferably 40-50m 2 / g.
3. The modified silicon-aluminum material according to claim 1, characterized in that, The modified kaolin contains 30-48 wt% alumina, 30-52 wt% silicon dioxide, and 0-30 wt% modified metals (calculated as oxides). Preferably, the modified kaolin contains 30-48 wt% alumina, 37-52 wt% silicon dioxide and 1-15 wt% modified metal.
4. The modified silicon-aluminum material according to any one of claims 1-3, characterized in that, The density of weakly alkaline sites on the surface of the modified kaolin is 80-600 μmol / g; the density of moderately alkaline sites is 120-1600 μmol / g; and the density of strongly alkaline sites is 80-1400 μmol / g. The surface alkaline sites correspond to the CO2 desorption temperature in the CO2-TPD test, and the surface acidic sites correspond to the NH3 desorption temperature in the NH3-TPD test. Preferably, the density of weakly acidic sites on the surface of the modified kaolin is 0.04-5 μmol / g.
5. The method for preparing modified kaolin according to any one of claims 1-4, characterized in that, include: (1) Kaolin is calcined at 400-1200℃ for 0.5-10h to obtain metakaolin; (2) Mix metakaolin with water to obtain metakaolin slurry, and process the metakaolin slurry with a shearing machine to obtain slurry metakaolin; (3) Mix peroxide, inorganic-organic composite alkali, ionic surfactant, quinoline substances and oil in a mass ratio of 1:0.1-18:0.5-5:0.4-5:0.1-8, and adjust the pH of the mixture to 9-14 to obtain etching solution; (4) Mix the etching solution and the slurry metakaolin evenly, wherein the mass ratio of the etching solution to the metakaolin is 0.2-3:
1. During the mixing process, a modified metal salt solution may or may not be added to obtain a modified mixture. (5) The modified mixture is filtered, washed, dried and calcined to obtain modified kaolin.
6. The method for preparing modified kaolin according to claim 5, characterized in that, In step (3), the peroxide is one or more of H2O2, Na2O2 and peracetic acid; The inorganic-organic composite alkali is a mixture of inorganic and organic alkalis. The inorganic alkali is selected from one or more of sodium hydroxide, potassium hydroxide, ammonia, sodium phosphate, anhydrous borax, anhydrous sodium carbonate, anhydrous potassium carbonate, sodium silicate, sodium orthosilicate, and sodium acetate. The organic alkali is selected from one or more of proline betaine, trigonelline, alanine betaine, valine betaine, pipecolic acid betaine, aminopentabetaine, N-trimethyllysine, arsine betaine, γ-butyryl betaine, and ergothioneine. The ionic surfactants mentioned above are selected from carboxylic acids, sulfonic acids, sulfuric acids, amino acids and their salts with hydrophilic groups and branched or straight-chain hydrocarbons with C10-C16 hydrophobic groups. The quinoline substances mentioned are selected from one or more of 4-hydroxyquinoline, 8-hydroxyquinoline, quinolinone, acetaminophenquinoline, and quinine; The oil is selected from one or more of naphtha, lubricating oil, jet fuel, kerosene, diesel oil, peanut oil, perilla oil, and tea tree oil.
7. The method for preparing modified kaolin according to claim 6, characterized in that, In step (3), the peroxide is hydrogen peroxide and / or peracetic acid; the inorganic base is ammonia, sodium hydroxide or sodium phosphate; the organic base is proline betaine or γ-butyryl betaine; the ionic surfactant is potassium dodecylbenzenesulfonate, hexadecyltrimethylammonium chloride or dodecylamine; the quinoline substance is 4-hydroxyquinoline or quinoline ketone; and the oil is selected from one or more of lubricating oil, naphtha and diesel.
8. The method for preparing modified kaolin according to claim 5, characterized in that, In step (4), a modified metal salt solution is added. The modified metal salt solution is selected from aqueous solutions of chloride, nitrate, sulfate or phosphate salts of IA, IIA, IVB, lanthanide metals; the mass concentration of the metal salt is 5-30 wt%.
9. The method for preparing modified kaolin according to claim 5, characterized in that, In step (1), the roasting temperature is 600-900℃; the roasting time is 2-6h; In step (2), the mass ratio of kaolin to water is 1:0.5-20, preferably 1:2-10; the particle size of the solid particles in the slurry metakaolin treated by the shearing machine is 5nm-20μm, preferably 10nm-15μm; In step (3), the mass ratio of peroxide, inorganic-organic composite alkali, ionic surfactant, quinoline-like substance and oil is 1:0.2-6:0.5-3:0.4-2:0.3-5; the temperature for preparing the etching solution is 0-35℃, preferably 10-25℃; the mixture is stirred using a stirrer at a speed of 50-1000 rpm, preferably 300-1000 rpm; the stirring time is 0.5-10h, preferably 1-3h. In step (4), the pumping speed for injecting the modified metal salt solution into the mixture of etching solution and slurry metakaolin is 0.1-20 mL / min, preferably 0.5-10 mL / min.
10. The method for preparing modified kaolin according to claim 5, characterized in that, In step (5), the drying temperature of the mixture is 80-150℃, preferably 100-120℃; the calcination temperature is 400-1000℃, and the calcination time is 1-10h; preferably, the calcination temperature is 500-900℃, and the calcination time is 2-5h.
11. The use of the modified kaolin according to any one of claims 1-4 in catalysts, fillers, ceramics, coatings, pharmaceuticals and textiles.
Citation Information
Patent Citations
Method for modifying kaolinite
CN100478069C
Method for modifying kaolin
CN102188963A
Preparation method of tower bottom oil catalytic cracking cocatalyst
CN105983449A
Macroporous kaolinite, preparation and applications thereof
CN109692702A